2017
DOI: 10.1016/j.ebiom.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of PKCθ Counteracts Muscle Disease in a Mouse Model of Duchenne Muscular Dystrophy

Abstract: Inflammation plays a considerable role in the progression of Duchenne Muscular Dystrophy (DMD), a severe muscle disease caused by a mutation in the dystrophin gene. We previously showed that genetic ablation of Protein Kinase C θ (PKCθ) in mdx, the mouse model of DMD, improves muscle healing and regeneration, preventing massive inflammation. To establish whether pharmacological targeting of PKCθ in DMD can be proposed as a therapeutic option, in this study we treated young mdx mice with the PKCθ inhibitor Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 67 publications
(88 reference statements)
3
36
0
Order By: Relevance
“…We previously showed that knock-out of PKCθ or its inhibition in a mouse model of Duchenne Muscular Dystrophy (mdx mouse) reduces muscle damage, by modulating the immune cell infiltration. This beneficial effect was mainly due to the inhibition of PKCθ in T cells, which leads to reduced inflammation [10][11][12]. Interestingly, we also found that lack of PKCθ promotes muscle repair in dystrophic mice, even at advanced stages of the disease, supporting SCs survival and maintenance [13].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…We previously showed that knock-out of PKCθ or its inhibition in a mouse model of Duchenne Muscular Dystrophy (mdx mouse) reduces muscle damage, by modulating the immune cell infiltration. This beneficial effect was mainly due to the inhibition of PKCθ in T cells, which leads to reduced inflammation [10][11][12]. Interestingly, we also found that lack of PKCθ promotes muscle repair in dystrophic mice, even at advanced stages of the disease, supporting SCs survival and maintenance [13].…”
Section: Introductionsupporting
confidence: 56%
“…We next sought to validate our results from the PKCθ-/-mouse model, using the C20specific inhibitor of PKCθ [11,12,18,19]. To analyze the effects of C20 throughout the different phases of myogenic progression, we isolated SC from WT and PKCθ-/-mice and cultured them for 4 days in growth medium (GM), followed by 2 days in differentiation medium (DM).C20 was used at the concentration range (0.5 µM, 1 µM and 2 µM) we previously found not to be toxic for in vitro treatment [11]. Control cultures were treated with 0.1% DMSO, the same concentration used for C20 dilution.…”
Section: Pharmacological Inhibition Of Pkcθ Increases the Fraction Ofmentioning
confidence: 99%
“…Other studies investigating cardiac transplant rejection and cardiac muscle structure in dystrophic mice identified and characterized novel derivatives of 2,4-diaminopyrimidine and 2,4-diamino-5-nitropyrimidine as selective inhibitors against PKCθ [149][150][151]. Treatment with these compounds reduced inflammation in dystrophic mice, and prolonged graft survival in an in vivo rat heterotopic cardiac transplant model.…”
Section: Inhibiting Novel Pkcs In Heart Disease and After Heart Transmentioning
confidence: 99%
“…We previously showed that lack or pharmacological inhibition of PKCθ reduced muscle loss and inflammation, and increased muscle regeneration and performance in mdx mice. The observed phenotype was primarily due to lack of PKCθ in hematopoietic cells [19,20], and in particular inhibition of early T cells infiltration in dystrophic muscle [21]. However, PKCθ is also expressed in muscle, where it modulates several signalling pathways involved in foetal and early post-natal tissue growth and maturation [22][23][24].…”
Section: Introductionmentioning
confidence: 99%